Effect of Indole-3-Acetic Acid (IAA) on Biochemical Responses of Cowpea (Vigna unguiculata (L.) Walp) Var. Bari Fellon-1 (Bangladesh Journal of Scientific and Industrial Research, 2011)
The biochemical responses of Cowpea to IAA treatments (foliar spray) with different concentrations (20 ppm, 40 ppm, 60 ppm and 80 ppm) were studied. Biochemical parameters such as leaf pigments, moisture, ash, crude fiber, calorie, protein, fat, carbohydrate and nitrogen free extract (NFE) contents in seeds of Cowpea were studied in the experiment. Different biochemical parameters responded differently following IAA treatments. Highest protein content (22.7%) and ash content (4.2%) were recorded from the seeds of the plants treated with 80 ppm IAA. Highest carbohydrate content (60.8%) and calorie content were recorded from the seeds of the plants treated with 60 ppm IAA. Moisture content was decreased due to all IAA treatments. Fat, crude fiber and NFE content of seeds also found to be varied with different treatments. Out of all the treatments, the best stimulation was found for 60 ppm IAA treatment. The results of the present work also indicate that an appropriate concentration of IAA can be fruitfully utilized to produce better quality of seeds and leaf pigments of Cowpea. Key words: Auxins; Biochemical response; IAA treatment; Cowpea DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8110 Bangladesh J. Sci. Ind. Res. 46(1), 77-82, 2011